Kedudukan Krama Desa yang Beralih Agama dalam Tanah Karang Desa di Desa Adat Canggu Badung - I Komang Suartama Yasa (Jurnal Preferensi Hukum, 2020)
The status and function of customary land causes land problems to become complex, which can be a source of legal and social problems that appear in various forms of land disputes. Likewise with respect to the village plots, it is not free from disputes. There are many factors that lead to the disputes in village yards. The objectives of this study is to examine the rights and obligations of the village manners who occupy the village reef land and to examine the position of the village manners who are no longer Hindu towards the village coral land are in accordance with the Canggu Badung Adig village awig-awig. The type of study used is empirical legal research. The results of this study is 1) the rights and obligations of the village manners who occupy the village reef land in accordance with awig- awig Adat Canggu Badung Village is to occupy the village coral land, bearing in mind the village manners who occupy the village coral land have been regulated in Awig-Awig Canggu Adat Village, Pawos 4 Paragraph (1) and is obliged to participate in retribution, carrying out village directives and paying contributions. 2) The position of the village manners who are no longer Hindu towards the village coral land is in accordance with the awig-awig of the Traditional Village of Canggu Badung every village manners who convert, then the manners are called tamiu manners. Based on this, all the assets or facilities of the customary village must be returned to the customary village, including the village coral land it occupies, as stated in the Pararem of the Canggu Customary Village, Pawos 4 Paragraph (3).